The incidence of periungual desquamation and thrombocytosis in Kawasaki disease and the importance of systematic observation in the subacute phase - Kim, Beom Joon; Choi, Arum; Kim, Sukil; Han, Ji-Whan (Frontiers in Pediatrics, 2024)
Background: Periungual desquamation and thrombocytosis are characteristic of the subacute phase of Kawasaki disease (KD). However, accurate observations of periungual desquamation and thrombocytosis are lacking. Methods: This retrospective study included patients with acute-phase KD who received treatment at seven affiliated university hospitals in Korea between 2015 and 2017. Data were extracted from an anonymized registry established by the Korean Society of Kawasaki Disease. We investigated whether the findings of patients observed according to a set protocol until the subacute stage (group I) were different from those of patients observed without the use of a protocol (group II). Results: A total of 879 patients with KD were included in the analysis. Periungual desquamation was observed in 85% and 12.7% of patients in groups I and II, respectively. Thrombocytosis was observed in 76.7% and 44.7% of patients in groups I and II, respectively. Furthermore, compared to the initial test, the platelet counts of patients increased 100% and 67.9% in group I and II, respectively. When incomplete KD was defined only by the main symptoms during the acute stage and the diagnostic criterion of periungual desquamation during the subacute stage was excluded, the significant difference in the incidence of incomplete KD between groups I and II was no longer apparent. Conclusion: Performing regular and detailed observations has resulted in a higher incidence of periungual desquamation and thrombocytosis during the subacute phase of KD than those reported in recent studies. This indicates that until now, we have been neglecting the observation of symptoms and signs during the subacute phase. Regular monitoring during this period can also aid in differentiating suspected cases of KD and facilitate appropriate follow-up of complications.